2012
DOI: 10.1111/j.1752-4598.2012.00197.x
|View full text |Cite
|
Sign up to set email alerts
|

Strong divergences in regional distributions in Romania: recent ecological constraints in dragonflies (Odonata) versus ancient biogeographical patterns in butterflies (Lepidoptera: Rhopolocera)

Abstract: 1. While the biogeographical structuring of Europe as a whole is already relatively well understood, patterns at the more regional scale are still poorly explored. Especially the influence of differing ecological demands among species groups on regional distribution patterns is mostly unresolved. Therefore, we compare the distributions of strictly terrestrial butterflies with those of semi-aquatic dragonflies.2. We analysed a regionalised distribution of the 196 butterfly and 68 dragonfly taxa of Romania with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In the south, the ranges of the two clades appear separated just by the Danube at the Iron Gates, from where the colonization could have started. The part of Carpathians close to Iron Gates is significant within Romania for occurrence of species with Mediterranean affinities (Cameron et al, 2016;Grossu, 1984;Hurdu et al, 2016;Iftime, 2005;Rákosy, Heiser, Manci, & Schmitt, 2013), so it might have been suitable for warm-demanding species also in the past. In a widespread congeneric species H. pomatia, Korábek et al (2018) found a mitochondrial lineage whose distribution also suggests survival in the south-western F I G U R E 5 Hypothetical extent of glacial refugia of Caucasotachea vindobonensis and Helix thessalica (dashed lines) and areas, from which they most likely postglacially colonized the central and eastern Europe (solid lines).…”
Section: Inferred Sources Of Postglacial Expansionmentioning
confidence: 99%
“…In the south, the ranges of the two clades appear separated just by the Danube at the Iron Gates, from where the colonization could have started. The part of Carpathians close to Iron Gates is significant within Romania for occurrence of species with Mediterranean affinities (Cameron et al, 2016;Grossu, 1984;Hurdu et al, 2016;Iftime, 2005;Rákosy, Heiser, Manci, & Schmitt, 2013), so it might have been suitable for warm-demanding species also in the past. In a widespread congeneric species H. pomatia, Korábek et al (2018) found a mitochondrial lineage whose distribution also suggests survival in the south-western F I G U R E 5 Hypothetical extent of glacial refugia of Caucasotachea vindobonensis and Helix thessalica (dashed lines) and areas, from which they most likely postglacially colonized the central and eastern Europe (solid lines).…”
Section: Inferred Sources Of Postglacial Expansionmentioning
confidence: 99%
“…D). In general, such mountain butterflies are typical faunal elements of the Carpathians and strongly contribute to their biogeographical differentiation when compared with adjacent low‐lying regions (Rákosy et al ., ).…”
Section: The Carpathians As a Biodiversity Hotspotmentioning
confidence: 99%
“…On the other hand, Zygoptera in NYS demonstrate the more typical post-Eocene tropical conservatism pattern (Weins & Donoghue, 2004;Weins et al, 2006) and these odonates are relative newcomers to Eastern/central NA compared to many of the much older endemic dragonflies (Figs 2 and 3). This alternate subordinal pattern might not occur in Eurasia, however (Heiser & Schmitt, 2013), where the signature of historical biogeographical patterning appeared to be weak at broad regional (100 000s km 2 ) scales (Rakosy et al, 2012). Despite their tiny size, certain damselflies' remarkable colonisation abilities (e.g.…”
Section: Tropical and Temperate Conservatismmentioning
confidence: 99%
“…Rather, the overriding pattern for Odonata is the preponderance of non-ecological speciation mechanisms (i.e. sexual selection) as drivers of diversity (Misof, 2002;McPeek & Gavrilets, 2006;Davis et al, 2011;Svensson, 2012), while there is also some support for the waterenergy hypothesis (Keil et al, 2008;Rakosy et al, 2012).…”
Section: Introductionmentioning
confidence: 99%